IMPLEMENTACIÓN DE UN SERVIDOR NAS CON Own-Cloud y NoIP EN UN ORDENADOR RASPBERRY PI A LA EMPRESA HYDROEVAL INGENIEROS CONSULTORES - RÍOS SIERRA, RENEÉ RONALD (2020)
The company Hydroeval Ingenieros Consultores S.R.L. Located in the city of Lima, at Avenida Javier Prado Este No. 309 Floor 10, it is a Consulting Engineering company, formed by private investment, which has directed its greatest effort in solving problems of a consultant specialized in the Energy departments, water, road, sanitation, hydro-oceanographic studies, hydrometry and inspection and control. It also carries out basic studies of Geodesy, topography, hydrography, cadastre, geology, soil mechanics, offering high-quality and high-efficiency services to both private companies and governmental and non-governmental institutions. Its activities are mostly in the field for data collection, to then be processed in the cabinet and drawings are made through engineering design programs and subsequently the corresponding reports of the work carried out to deliver to clients. These activities have been running smoothly for a long time from the start of the company, since the work that was carried out was in a conventional way, but the technology is more sophisticated and the work systems more bureaucratic due to the requirements and procedures that were carried out before. to start a job or project in recent years, making this information more and heavier, administratively and technically, it is not usual to find advanced engineering programs anywhere in particular. Due to this, unfavorable events are occurring at the time of carrying out the work, whether due to the failure of a computer equipment, the failure of a program or software, lack of documentation to be presented in the same work area, etc. Any condition that does not allow the project to start in the administrative, computer and technological fields. The company is obliged to implement a device capable of uploading, downloading files and programs necessary to carry out work from any device or place through the network, and which is economical and efficient, taking advantage of the fact that today, a common person and all the more reason for a company to have internet service.